Endoscopic Treatment for Gastric Antral Vascular Ectasia: Current Options - Zepeda-Gómez,Sergio (2017)
Gastric antral vascular ectasia (GAVE) is a capillary-type vascular malformation located primarily in the gastric antrum. Patients can present with iron-deficiency anemia, overt gastrointestinal bleeding, or both. Diagnosis and characterization is made at endoscopic examination, and the preferred management of patients with GAVE is endoscopic therapy. Herein, we present a review of the evidence about the efficacy, complications, and outcomes of the most frequently used endoscopic therapies for GAVE